Synthesis of biofunctional coating for a TiZr alloy: Surface, electrochemical, and biological characterizations - Cordeiro, Jairo M.; Pantaroto, Heloisa N.; Paschoaleto, Emanuella M.; Rangel, Elidiane C. [UNESP]; Cruz, Nilson C. da [UNESP]; Sukotjo, Cortino; Barão, Valentim A.R. (Elsevier, 2018)
This study formed a biofunctional coating for a Ti15Zr alloy to improve the surface characteristics, the electrochemical behavior, and the biological properties of this implant material. Ti15Zr discs (15 mm in diameter × 1 mm thickness) were obtained in three versions: machined, SLA®-treated (control groups), and modified by plasma electrolytic oxidation (PEO) (experimental group). Surface features such as topography, composition, surface roughness, surface free energy, and hardness were assessed. Electrochemical tests were conducted with body fluid solution (pH 7.4). The albumin protein adsorption was measured by the bicinchoninic acid method, and the adhesion of Streptococcus sanguinis was determined. The surface treatments modified the material's topography. SLA promoted surface roughness higher than that of the other groups, whereas PEO surfaces presented the highest values of hardness and surface free energy. PEO increased the polarization resistance and the corrosion potential, and decreased capacitance and corrosion current density values. In addition, plasma treatment improved the albumin adsorption without being favorable to biofilm adhesion. PEO appears to be the most promising alternative for Ti15Zr alloys, since it improved surface characteristics and electrochemical behavior, as well as enhancing the adsorption of albumin on the material surface with fewer tendencies to bacterial adhesion.
Keywords: Alloys; Biofilms; Corrosion; Dental implants; Proteins; Titanium